Characteristics of Self-Rated Oral Health among Syrian Refugee Parents in Ontario - Aseel Alzaghoul; Parmin Rahimpoor-Marnani; Khalid Yunis; Akm Alamgir; Baraa Alghalyini; Hala Tamim (Hindawi Limited, 2023)
Background. Canada has been hosting Syrian refugees since early 2015. Almost half of the Syrian refugee population lives in Ontario, with dental health being at the top of the list of important immediate needs. The objective of the study was to evaluate self-rated oral health and its associated factors among Syrian refugee parents residing in Ontario. Methods. This was a cross-sectional study where 540 Syrian refugee parents, residing in Ontario and with at least one child less than 18 years of age, were interviewed. Information about self-rated oral health was collected based on the question "In general, how would you rate the health of your teeth and mouth?" with answers ranging from 1 representing "excellent" and 5 representing "very poor." Multiple linear regression analysis was performed to assess the independent relationship between each of the sociodemographic-, migration-, health-, dental-related factors, and self-rated oral health. Results. The overall prevalence of poor and very poor self-rated oral health was 43.5%. The results showed that the presence of dental health insurance, private sponsorship, improved physical and mental health, and regular visits to the dentist were factors related to improved oral health. Discussion. To achieve better oral health outcomes among refugee populations, including Syrian refugees, efforts should be focused on improving dental care and dental insurance for vulnerable populations.